Behavioral Public Administration (BPA): The need for a New Field (Literature Review) - Gvantsa Dzidziguri (European Scientific Journal, ESJ, 2023)
Modern scientific literature agrees on the issue that it is impossible to perceive public administration as a separate field. Public administration as a field, by general definition, includes the implementation of public policy and the structure and work of various actors (state or non-state) involved in the implementation process. Due to the voluminous nature of the mentioned field, it is not appropriate to consider them separately, because the organizations involved in the process of public policy implementation are not self-generated structures but each organization relies on human resources. Therefore, in the agenda of the scientific space, together with the research in the field of public administration, there was a need to use the results of the research of behavioral science. The paper specifically deals with the issue of analyzing the necessity of behavioral public administration as a field, which is analyzed through a literature review. The sources used to analyze the mentioned issue include relevant scientific articles and books. The purpose of the study is to determine and analyze the connection between behavioral science and the field of public administration, and the effectiveness of their combination, which leads to the broader goal of the study, which should answer the question of the necessity and effectiveness of the existence of behavioral public administration as a field. The relevance of the research stems from the broad nature of the field of public administration, which puts on the agenda the need to combine the achievements of various adjacent fields.